Advancing Telephone Focus Groups Method Through the Use of Webinar: Methodological Reflections on Evaluating Ontario, Canada's Healthy Babies Healthy Children Program. (1st October 2015) - Chong, Eunice; Alayli-Goebbels, Adrienne; Webel-Edgar, Lori; Muir, Sarah; Manson, Heather
Telephone focus groups have been increasingly popular in public health research and evaluation. One of the main concerns of telephone focus groups is the lack of nonverbal cues among participants, which could limit group interactions and dynamics during the focus group discussion. To overcome this limitation, we supplemented telephone focus groups with webinar technology in a recent evaluation of a provincial public health program in Ontario, Canada. In this article, we share the methods used and our experiences in conducting telephone focus groups supplemented with webinar technology, including advantages and challenges. Our experience will inform other researchers who may consider using telephone focus groups with webinars in future research and evaluation.